Efficacy and prognosis analysis of pulley traction-assisted endoscopic submucosal dissection with dental floss for early gastric cancer and precancerous lesions - Luo, Hao; Tang, Jie; He, Xiaotong; Shi, Yinglei; Chang, Yunli (Frontiers in Surgery, 2025)
ObjectiveTo investigate the clinical efficacy of pulley traction-assisted endoscopic submucosal dissection (ESD) with dental floss in patients with early gastric cancer and precancerous lesions, and its impact on patient prognosis.MethodsClinical data of 77 patients with early gastric cancer and precancerous lesions were retrospectively analyzed. The patients were divided into groups according to different treatment regimens; 38 patients in the control group underwent ESD, whereas 39 patients in the study group underwent pulley traction-assisted ESD with dental floss. Lesion resection status, perioperative indicators, gastrointestinal function indicators, complications, and recurrence were compared between the two groups.ResultsThe curative and en bloc resection rates in the study group were significantly higher than those in the control group, whereas the residual rate of basal lesions was significantly lower than that in the control group (P < 0.05). The study group experienced less intraoperative bleeding and had a significantly shorter operative time, anal exhaust time, first eating time, and length of hospital stay (P < 0.05). Three days postoperatively, motilin (MTL), gastrin (GAS), pepsinogen I (PG I), and pepsinogen II (PG II) levels were significantly reduced in both groups, with significantly higher levels in the study group (P < 0.05). The incidence of complications in the study group was 7.69% (3/39), which was significantly lower than that in the control group [26.32% (10/38); P < 0.05]. Three months postoperatively, the quality of life scores (FACT-G) in all aspects significantly increased in both groups, with the study group showing significantly higher scores (P < 0.05). The recurrence rate at 12 months postoperatively in the study group (5.13%) was significantly lower than that in the control group (23.68%; P < 0.05).ConclusionPulley traction-assisted ESD with dental floss is effective in treating early gastric cancer and precancerous lesions.